An insect acetylcholinesterase biosensor utilizing WO3/g-C3N4 nanocomposite modified pencil graphite electrode for phosmet detection in stored grains. (1st June 2021) - Bilal, Sehrish; Mudassir Hassan, M.; Fayyaz ur Rehman, Muhammad; Nasir, Muhammad; Jamil Sami, Amtul; Hayat, Akhtar
Highlights: WO3 /g-C3 N4 was used to construct a novel AChE/PGE biosensor. Biosensor permitted to detect Phosmet with a detection limit of 3.6 nM. The developed biosensor showed recovery between 92 and 99% for wheat samples. In vivo repellency bioassay determined the efficacy of Phosmet against T. castaneum. Computational analysis explored the structural topographies for enzyme-inhibitor interaction. Abstract: This study was undertaken to assess the potential of Tribolium castaneum (Red flour beetle) acetylcholinesterase (Tc-AChE) based electrochemical biosensor integrating WO3 /g-C3 N4 nanocomposite modified Pencil graphite electrode to detect an organophosphate insecticide, Phosmet. The WO3 /g-C3 N4 nanocomposite provides a non-toxic, biocompatible surface for binding the enzyme on the electrode surface, attributed to its large surface area, high conductivity, and low ohmic resistance. The proposed biosensor shows a very good analytical performance with LOD 3.6 nM for Phosmet and effectively determined Phosmet in wheat with a 99% recovery rate. Furthermore, molecular docking deciphers the binding interactions of Phosmet with Tc-AChE using a modified AutoDock LGA algorithm and an AMBER03 force field in YASARA. The kinetic parameters strongly suggest the high potency of inhibitor with the enzyme. This study presents an adaptable, rapid, and straightforward approach that opens ways towards real progress in developing commercial biosensors for pesticide detection.